The Role of Multicultural Islamic Education in Building National Unity Towards a Golden Indonesia in 2045: Peran Pendidikan Islam Multikultural dalam Membangun Persatuan Nasional Menuju Indonesia Emas 2045 - Aqodiah, Aqodiah; Mappanyompa, Mappanyompa; Sahwan, Sahwan; Hidayatussaliki, Hidayatussaliki (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Indonesia’s multicultural reality, characterized by diverse ethnic, religious, linguistic, and cultural identities, represents both a national asset and a challenge for sustaining social cohesion. Specific Background: Increasing intolerance, discrimination, and socio-cultural disparities indicate that diversity has not been fully optimized as a foundation for national development. Knowledge Gap: Existing studies largely examine multiculturalism in fragmented sectors without systematically linking it to the Indonesia Emas 2045 development roadmap or providing an integrative analytical framework. Aims: This study aims to analyze the role of multicultural Islamic education in strengthening national unity and to formulate a strategic framework supporting inclusive and sustainable development toward Indonesia Emas 2045. Results: The findings demonstrate that multiculturalism functions as strategic social capital by reinforcing Pancasila values, promoting tolerance through education, strengthening social cohesion, and supporting inclusive policies, with additional contributions from family roles, digital literacy, and cross-sector collaboration. Novelty: This study offers an integrative framework connecting multicultural dynamics, national identity formation, and long-term development planning within a unified roadmap aligned with Indonesia Emas 2045. Implications: The study provides a conceptual and practical basis for developing multicultural Islamic education curricula, inclusive governance strategies, and diversity-based development policies to maintain national unity and global competitiveness. Highlights• Multicultural values integrated into education address polarization and identity conflicts• Social capital derived from diversity supports inclusive development strategies• Cross-sector collaboration and digital literacy strengthen cohesive society KeywordsMulticultural Islamic Education; National Unity; Indonesia Emas 2045; Social Capital; Inclusive Development